Awakening the soul during travel: influence mechanism of memorable tourism experience on university students’ life meaning - Su, Qiaolan (Frontiers in Psychology, 2025)
In recent years, the mental health issues of university students have received increasing attention. Research has shown that meaningful life experiences, such as memorable tourism experiences, can enhance individuals’ sense of meaning in life and promote mental health. This study explores the mechanisms through which memorable tourism experiences influence the sense of meaning in life among university students, focusing on the mediating roles of positive affect, self-reflection, and personality traits, as well as the moderating role of gender. Using a questionnaire survey, data were collected from 880 university students. Validated scales, including the “Memorable Tourism Experience Scale, ““Positive Affect Scale,” “Self-Reflection Scale,” “Personality Trait Scale,” and “Meaning in Life Scale,” were employed to measure key constructs. Data were analyzed using structural equation modeling (SEM) and multi-group analysis to test the hypothesized relationships and moderating effects. The results indicate that memorable tourism experiences have a significant positive impact on university students’ sense of meaning in life. Positive affect, self-reflection, and personality traits all partially mediate this relationship, with positive affect exhibiting the strongest mediating effect, while personality traits show relatively weaker mediation. Furthermore, gender moderates the relationship between memorable tourism experiences and positive affect, as well as the relationship between personality traits and meaning in life. These findings support Self-Determination Theory, demonstrating that memorable tourism experiences can fulfill individuals’ basic psychological needs and enhance their sense of meaning in life through multiple psychological mechanisms. This study provides practical insights for mental health interventions targeting university students, particularly highlighting the importance of reflective activities and personalized support in amplifying the psychological benefits of positive experiences.